TIPIBA SEBAGAI METODE PEMBELAJARAN MEMBACA PERMULAAN - Wawan Gunawan (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2012)
ABSTRACT This article offers new method of learning in reading for beginner. The name of this method is TIPIBA. There are three principles in TIPIBA. The first is principle of imitation, namely  is students imitate the sound of teacher’s spoken about syombol of writing. The second is principle of thought, namely  is students think of ways to voice emblem posts. The third is the principle of reading, namely is students reading symbols to understand the meaning of its. For thats, there are three components, namely the main  material, learning material, and the strip material.TIPIBA formulated on the basis of psychology, linguistics, teaching and learng methodology, and nature of reading for beginner. Keywords: imitation, thinking, reading